Pengaruh Senam Bugar Lansia Terhadap Kekuatan Otot Wanita Lajut Usia Tidak Terlatih di Yogykarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT The fitness exercise for the elderly (FDE) created by Persatuan Wanita Olahraga Indonesia (Perwosi) Yogyakarta, consist of A, B, C and D series. The FDE-D belongs to a low impact, an aerobic exercise with light to moderate intensity, rich in movements opposing the gravitational force. The old age has a decline skeletal muscles strength. The aims of this study is to examine the effects of FDE-D on muscle strength in non-trained old women. The sample consists of 30 old women of Yogyakarta, aged 60 - 70 years old who were healthy, and non-trained. They were divided into three groups, each consisting of 10 women, namely: Group I (G I) was treated FDE - D 3 days a week